KEANEKARAGAMAN JENIS BURUNG DI HUTAN ADAT IMBO PUTUI DESA PETAPAHAN KABUPATEN KAMPAR - Muhammad Vikko Alshar; Defri Yoza Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Bird in Indonesia is a protected animal and one of the biodiversity that must be preserved from extinction and the decline in species diversity which has an important role in the forest ecosystem. The purpose of this research was to determine the diversity of bird species found in Imbo Putui Customary Forest in Petapahan Village, Kampar Regency. This study uses a the point count method by following a predetermined transect path, which is divided into three observation paths. Parameters observed included bird species, number of birds, time of encounter and bird activity. The results showed that the diversity of bird species found in Imbo Putui Customary Forest was 30 bird species from 19 families. The index of bird species diversity in the Imbo Putui Indigenous Forest area shows 3.11 with a high category and the Relative Abundance Value (IKR) of bird species in each Imbo Putui Customary Forest area is low. Keywords : Bird, customary forest, animals.